Bibliometric Analysis of Risk Management in Islamic Microfinance - Firmansyah, Irman; Prayudya, Daffa Rizqi (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2025)
Research on risk management in Islamic microfinance remains relatively underdeveloped despite the sector’s growing strategic importance in supporting financial inclusion, poverty alleviation, and Shariah-compliant economic empowerment. This study employs a comprehensive bibliometric analysis to map the intellectual structure, thematic evolution, and global collaboration patterns of research on risk management within Islamic microfinance from 2000 to 2025. Using Scopus-indexed data and Biblioshiny, the analysis examines publication trends, co-citation networks, keyword co-occurrence, thematic mapping, and country collaborations. The findings indicate that the literature is still in an early conceptual phase, dominated by foundational discussions on Islamic finance stability rather than specific risk-related issues at the micro level. Co-citation networks reveal reliance on classic works, while thematic maps show an absence of well-developed motor themes on risk management. Collaboration patterns are concentrated in a few countries such as Indonesia, Malaysia, and the United Kingdom, with limited contributions from regions traditionally central to Islamic finance. These results highlight a significant research gap between the increasing complexity of risks faced by Islamic microfinance institutions—such as credit risk, operational risk, and Shariah compliance risk—and the limited academic attention devoted to developing robust, context-specific risk management frameworks. This study provides critical insights that can guide future research agendas, especially on digital risk mitigation, Shariah governance frameworks, comparative risk modeling, and the integration of emerging technologies such as artificial intelligence. The findings contribute to strengthening the epistemic foundation of Islamic microfinance and supporting its long-term sustainability in a rapidly evolving financial landscape.